AI Adoption in the Chinese Food and Beverage Industry: An Exploratory Study - Wei, Yuling; Simay, Attila Endre (President University, 2023)
This study aims to investigate the phenomena of how artificial intelligence (AI) as one of the cutting-edge technologies benefits restaurant services and what the obstacles to implementing AI in a restaurant are. Due to the rapid pace of life, people tend to have less and less eating time, especially white-collar workers. More and more restaurants implement AI technology to improve their cooking efficiency and reduce service time, such as fast payment systems (QR and facial recognition payment), AI-enabled bots, AI-powered self-ordering kiosks, and robot chefs. Since the COVID-19 pandemic begins in early 2020, food safety and sanitation become increasingly important when people eat outside. Chef and waiter robots are good options for avoiding intimate contact. This study employed qualitative research with in-depth interviews. We interviewed three restaurant managers in China. The findings suggest that adopting AI technology in restaurant services can minimize high costs, better manage customer relationships, and provide more convenient in-store services. This study contributes to the managerial gap in AI restaurants.